2005
DOI: 10.1158/1078-0432.ccr-1004-0015
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy of Solid Tumors by Targeting Extra Domain B Fibronectin: Identification of the Best-Suited Radioimmunoconjugate

Abstract: Purpose: The expression of extra domain B (ED-B) fibronectin is always associated with angiogenic processes and can be exclusively observed in tissues undergoing growth and/or extensive remodeling. Due to this selective expression, ED-B fibronectin is an interesting target for radioimmunotherapy of malignant diseases. The aim of this study was to identify the most appropriate ED-B-targeting radioimmunoconjugate for the therapy of solid tumors. Experimental Design: Three ED-B fibronectin-binding human antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 33 publications
5
88
1
Order By: Relevance
“…This ratio was reduced at 72 h, but still remained high at 9.4. In another study comparing the biodistribution of 125 I-L19-SIP and 111 In-L19-SIP in mice bearing the F9 teratocarcinoma tumours, Berndorff et al (2005) found that although tumour uptake was equal with both radionuclides, tumour to non-tumour ratios were higher for the 125 I-labelled antibody.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This ratio was reduced at 72 h, but still remained high at 9.4. In another study comparing the biodistribution of 125 I-L19-SIP and 111 In-L19-SIP in mice bearing the F9 teratocarcinoma tumours, Berndorff et al (2005) found that although tumour uptake was equal with both radionuclides, tumour to non-tumour ratios were higher for the 125 I-labelled antibody.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that, in this study, significant results were obtained with doses lower than that used in other RIT studies with the L19-SIP antibody. Berndorff et al (2005) reported that a single injection of 74 MBq 131 I-L19-SIP to F9 tumour-bearing mice resulted in a 10-day tumour growth delay and a median survival of 22 days; 13 days longer than that of control mice. More recently, Tijink et al (2006) also demonstrated that a single dose of 74 MBq 131 I-L19-SIP caused a maximum reduction in FaDu tumour size at day 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative analysis of the L19 antibody in scFv, full immunoglobulin G (IgG), and small immunoprotein (SIP) format identified L19SIP as the preferred format for RIT (27,(31)(32)(33). The molecular weight of L19-SIP in its nonreduced form is approximately 80 kDa.…”
Section: Introductionmentioning
confidence: 99%